2019
DOI: 10.4236/ape.2019.94016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Education Homework to Adolescent Girls’ Physical Activity in Finland

Abstract: Introduction: There is an urgent need for active strategies to promote physical activity (PA) among female adolescents, as they are at greater risk of physical inactivity. In addition to Physical Education (PE) in school, to reach adequate levels of PA, young people need to participate in PA during the school day and/or after-school hours and/or in the before-school period. One week of objectively measured and self-reported information enlightens the status quo of adolescent girls' PA and the role that PE home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 33 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Indeed, there has been only one short review of the literature (Hill, 2018 ). Seven empirical studies were found for this review, of which five considered homework as a source of PA as the sole or primary focus (Duncan et al., 2011 ; Duncan et al., 2019 ; Fairclough et al., 2013 ; Kääpä et al., 2019 , Kriemler et al., 2010 ), and two examined perceptions and attitudes (Pantanowitz et al., 2011 ; Smith & Madden, 2014 ; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, there has been only one short review of the literature (Hill, 2018 ). Seven empirical studies were found for this review, of which five considered homework as a source of PA as the sole or primary focus (Duncan et al., 2011 ; Duncan et al., 2019 ; Fairclough et al., 2013 ; Kääpä et al., 2019 , Kriemler et al., 2010 ), and two examined perceptions and attitudes (Pantanowitz et al., 2011 ; Smith & Madden, 2014 ; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There was considerable variation in quality among this sample, indicating caution should be maintained in interpreting findings. Four studies focused on the promotion of PA reported small positive associations between AH and PA levels (Duncan et al., 2011 ; Fairclough et al., 2013 ; Kääpä et al., 2019 ; Kriemler et al., 2010 ). However, the impact of interventions varied considerably.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations